Circular RNAs as disease modifiers of complex neurologic disorders - Galli, Veronica; Vinciguerra, Sara; Biagioli, Marta; Morandell, Jasmin (Frontiers in Pharmacology, 2025)
Circular RNAs are a large class of non-coding RNA molecules, conserved across species and produced by back-splicing. While their molecular functions are still elusive, the ones primarily retained in the nucleus are usually associated to regulation of transcription and mRNA processing patterns. Instead, the majority, are transported to the cytoplasm where they elicit micro-RNA (miRNA) or RNA binding protein (RBP)-sponging functions, or could be translated. CircRNAs are abundantly expressed in brain tissue, where they do not only act as regulators of brain development and physiology, but can also contribute to complex neurological conditions. In fact, deregulated circRNA expression levels were described in neurodevelopmental and neurodegenerative disorders, like Alzheimer’s disease, Parkinson’s disease and Huntington’s disease. Because of their described roles in pathology, these molecules may not only represent possible disease bio-markers, but they could even function as disease modifiers. As such, they could be targeted or protected in search of novel routes of therapeutic intervention. In this review, we highlight recent developments in the field, first discussing circRNAs involved in physiologic brain development and function, then reviewing studies that implicate circRNAs in neurodevelopmental and neurodegenerative disorders, with major attention to experimental studies exploring circRNA function and their role in neuropathologic processes. Such experimental strategies are mainly based on depletion or over-expression approaches and provide important insights into the modulatory potential of these molecules. They are relevant for clinical translation of basic research findings to drug development, possibly generating a positive impact for patients’ quality of life.